2021
DOI: 10.1111/aos.14792
|View full text |Cite
|
Sign up to set email alerts
|

Delayed diagnoses of Acanthamoeba keratitis at a tertiary care medical centre

Abstract: Methods: This retrospective study analysed all patients with culture-positive AK seen between 2012 and 2019 at a tertiary referral centre. Patient demographic information, clinical history, risk factors, symptom duration, referral patterns, slit lamp examination findings, visual acuity and need for surgery were collected. Results: The study included 45 eyes of 43 patients. On average, patients were symptomatic for 52.6 days before culture collection. Thirty-one percent of patients were diagnosed within 28 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
3
10
0
Order By: Relevance
“…In the PCR group, we found a significantly higher rate of suspected "bacterial infection." In the pre-PCR group, "herpetic keratitis" was the predominant initial diagnosis (48.3%), which is in line with the results of the literature [1,3,18,26,27].…”
Section: Clinical Findings and Initial Diagnosissupporting
confidence: 88%
See 1 more Smart Citation
“…In the PCR group, we found a significantly higher rate of suspected "bacterial infection." In the pre-PCR group, "herpetic keratitis" was the predominant initial diagnosis (48.3%), which is in line with the results of the literature [1,3,18,26,27].…”
Section: Clinical Findings and Initial Diagnosissupporting
confidence: 88%
“…Maybe it was not regularly available yet, as the included cases were from 2008 to 2011. Shah et al only included culture-proven AK cases and reported a mean time of 53 days from onset of symptoms to culture collection [18]. Data from the German Acanthamoeba Keratitis Registry indicate an exceptionally long delay until correct diagnosis of 2.8 months by a selection bias towards more difficult cases by tertiary referral centers which may also explain the high rate of corneal transplantations and thus histological confirmation (55%) in the registry [1].…”
Section: Duration Until Correct Diagnosismentioning
confidence: 99%
“…To the Editor, We read with interest the article by Shah YS et al "Delayed diagnoses of Acanthamoeba keratitis at a tertiary care medical center" [1].…”
mentioning
confidence: 99%
“…The article well describes difficulties to diagnose microbial keratitis. As reported in Table 1 , Acanthamoeba keratitis (AK) is usually misdiagnosed with herpetic keratitis [ 1 ]. We have had same and similar issues [ 2 , 3 ].…”
mentioning
confidence: 99%
“…5,12 These variable clinical presentations can result in misdiagnosis as herpetic keratitis in 38% to 48%, fungal corneal ulcer in 25.2%, and bacterial corneal ulcer in 3.9% of patients. 12,14…”
Section: Discussionmentioning
confidence: 99%